PENGARUH PEMBERIAN RUMPUT RAJA (Pennisetum purpupoides) DAN TEBON JAGUNG TERHADAP PERFORMANS SAPI PERANAKAN ONGOLE (PO) BETINA - ., Heryanto .; Maaruf, K; Malalantang, S S; Waani, M R (Universitas Sam Ratulangi, 2016)
THE EFFECTS OF AFFERING KING GRASS (Pennisetum Purpupoides) AND CORN STOVER ON PERFORMANCE OF ONGOLE CROSSBREED COWS A research evaluating the effects of affering king grass (Pennisetum purpupoides) and corn stover as feed ingredients on performance of ongole crossbreed cows has been conducled. Two years old, of fifteen ongole crossbreed cows with ± 200 kg body weight were used in this experiment. Completely Randomized Design with 5 treatments and 3 replications was used. The treatments were R1 = 100% king grass, R2 = 75% king grass + 25% corn stover, R3 = 50% king grass + 50% corn stover, R4 = 25% king grass + 75% corn stover and R5 = 100% corn stover. Variables measured were dry matter consumption (DMC), average daily gain (ADG) and feed conversion (FC). The average of DMC, ADG and FC were 4,64-5,97 kg/tail/day, 0,36-0,55 kg/tail/day and 10,89-13,44 respectively. The results showed that there were significant effects (P<0,05) on DMC and ADG, however, there was no significant effect (P>0,05) on FC. Tukey test showed that DMC of cows fed R1 were significantly (P<0,05) lower compared to R5, however, there was no significant (P>0,05) difference among cows fed R3, R4 and R5. ADG of cows fed R1 was not significantly (P>0,05) different compared to R2, R3 and R4, while, cows fed R1 and R2 were Significantly (P<0,05) lower compared to R5. Based on the results on DMC, ADG and FC it can be concluded that to increase performance of crossbreed cows the portion of king grass can be affered up to 50%, on the other hand corn stover is more than 50% in the ration. Key words : Kinggrass (Pennisetum purpupoides), corn stover, performance ongole crossbreed cows.